2018
DOI: 10.1007/s40094-018-0307-y
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and electro-optic properties of graphene oxide-doped hexylcyanobiphenyl liquid crystal

Abstract: Hexylcyanobiphenyl liquid crystal was doped with graphene oxide at ratios %0.25GO, %0.5GO, %1GO and %2GO, and the change in physical properties of pristine and the doped liquid crystals has been investigated. The phase transitions of prepared samples were studied by differential scanning calorimeter and polarized optical microscopy. The differential scanning calorimeter and polarized optical microscopy results are in good agreement when examining the nematic-isotropic liquid phase transition temperatures of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 35 publications
0
9
0
1
Order By: Relevance
“…Moreover, Lapanik et al reported a 30-50% reduction of the threshold voltage and switching time in partially reduced graphene oxide (PRGO)-doped nematic LCs and a 20-25% increment of the spontaneous polarization in PRGO-doped ferroelectric LCs [228]. Ozgan et al found that the dielectric anisotropy of nematic LC (6CB) would be increased with an increasing concentration of GO [115]. In a very recent investigation, Mrukiewicz et al systematically investigated the physical properties of nematic LC (5CB) dispersed with GO at a wide concentration range from 0.05 to 0.3 wt %.…”
Section: Modification Of Physical Properties Of Lc Materials By Nanodmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Lapanik et al reported a 30-50% reduction of the threshold voltage and switching time in partially reduced graphene oxide (PRGO)-doped nematic LCs and a 20-25% increment of the spontaneous polarization in PRGO-doped ferroelectric LCs [228]. Ozgan et al found that the dielectric anisotropy of nematic LC (6CB) would be increased with an increasing concentration of GO [115]. In a very recent investigation, Mrukiewicz et al systematically investigated the physical properties of nematic LC (5CB) dispersed with GO at a wide concentration range from 0.05 to 0.3 wt %.…”
Section: Modification Of Physical Properties Of Lc Materials By Nanodmentioning
confidence: 99%
“…In fact, it could be shown that the nanotubes can be reoriented elastically by reorienting the director through applied electric or magnetic fields. Fullerenes could effectively improve the switching speed of a nematic host LC [95], and improved electro-optic responses could be induced by doping graphene oxides in LCs [115].…”
Section: Introductionmentioning
confidence: 99%
“…A wide range of nanodopants has been used in studies on PLLCs including ferroelectric, 13 metal, 14 metal oxide 15 nanoparticles, quantum dots, 16 and carbon nanomaterials such as fullerenes, 17 carbon nanotubes, 18 and graphene oxide flakes. 19 For all cases, an improvement not only in the electro-optic but also in physical properties has been reported in many articles. For example, it has been shown that the threshold voltage and response times can be lowered; the dielectric anisotropy can be increased enhancing the effective anisotropy of the system; the nematic–isotropic phase transition temperature often becomes higher increasing the stability of the nematic phase.…”
Section: Introductionmentioning
confidence: 91%
“…Literatürde bu amaçla metalik nanopartiküller (Kobayashi et al 2006), ferromanyetik nanopartiküller (Okutan et al 2012), yarı iletken nanopartiküller (Zharkova and Streltsov 2020) ve karbon nanomalzemeler (Lee and Chiu 2001;Lee, Gau, and Chen 2005) gibi farklı tipte nanomalzemeler kullanılmaktadır. Özgan ve ark heksilsiyanobifenil sıvı kristaline grefen oksit nanoparçacık katkılandırarak ısısal ve elektro-optik özelliklerini incelemişlerdir (Özgan, Eskalen, and Tapkıranlı 2018). Karbon kuantum noktaları nematik sıvı kristale in elektro-optik performansına etkisi incelendi (Eskalen 2020).…”
Section: Introductionunclassified